Child Witchcraft Confession: Parental Reaction And Implication For Social Work Practice - ISANGHA, STANLEY OLOJI; OLAITAN, TAWAKALITU MARY; OGAR, L. E.; OBASI-IGWE, INYOMOMA. A.; AGHEDO, GABRIEL USIAGU; IWUAGWU, ANTHONY OBINNA (Advances in Social Sciences Research Journal, 2021)
Accusations of witchcraft, especially in Africa has often been directed towards the child and most parents has refused to play their role of a child protector which is essential in making or marring child development and this has become a source of increasing concern for social workers and other international human rights. This study was therefore designed to investigate the reactions of parents to child witchcraft confession in Akwa ibom State Nigeria. A qualitative study design using in-depth interviews was adopted. Thirty (30) in-depth interviews were held among parent’s which elicited information concerning child witchcraft confession. The qualitative data generated were content analyzed and the results indicated that majority of the parents are not ready to condone their children who confessed to witchcraft activities. The findings show that in spite of globalization, children who have a link with witchcraft activities are in jeopardy. The study therefore recommends some agenda for social work practitioners on the issue of witchcraft and child development.